KAJIAN TERHADAP KUALITAS BAHAN AJAR NON CETAK PROGRAM S1 PENDIDIKAN BIOLOGI DALAM PEMBELAJARAN INTERAKTIF SPJJ - Sekarwinahyu, Mestika; Rahayu, Ucu (LPPM Universitas Terbuka, 2009)
In an ODL system, the interactivity among a course material and students is part of learning process. The aim of this article is to get information from students of the quality of non printed course material as supplemented course material and to analyze the influence of the use of the non printed course material on students concept understanding. In this study, the non printed course materials are audio BMP of Human Anatomy and Physiology, Graphic audio of Biometry, and CAI of Biochemistry. Data was collected through instruments in forms of objective item test and questioners. The study showed that there were improvement of students understanding on concepts of Human Anatomy and Physiology by using audio BMP, concepts of Biometry by using Graphic audio, and concepts of Biochemistry by using CAI program. The gain of understanding between pre-test and post test was significant at ?=0.05. The quality of CAI of Biochemistry as interactive learning program was adequate. However, the quality of audio BMP of Human Anatomy and Physiology and Graphic audio of Biometry were still needed to be improved so it could be better interactive learning programs.